Becoming Salient: The TMT Leader's Role in Shaping the Interpretive Context of Paradoxical Tensions. Issue 3 (April 2017) - Knight, Eric; Paroutis, Sotirios
How do paradoxical tensions become salient in organizations over time? Ambidexterity and paradox studies have, thus far, primarily focused on how tensions inside organizations are managed after they have been rendered salient for actors. Using a longitudinal, embedded case study of four strategic business units within a media organization, we theorize the role of the top management team leader's practices in enabling tensions to become salient for their respective lower-level managers when there are initial differences in how tensions are interpreted across levels. Our findings extend a dynamic equilibrium model of organizing by adding interpretive context as an enabling condition that shapes the emergence of salience through the provision of a constellation of cues that guide sensemaking. Informed by a practice-based perspective on paradox, we also contribute a conceptual model of leadership as practice, and outline the implications for ambidexterity studies.